Barriers to Political Analysis in Aid Bureaucracies: From Principle to Practice in DFID and the World Bank - Yanguas, Pablo; Hulme, David (World Development, 2015)
Politics has become a central concern in development discourse, and ye t the use of political analysis as a means for greater aid effectivene ss remains limited and contested within development agencies. This art icle uses qualitative data from two governance “leaders” – the United Kingdom Department for International Development and the World Bank – to analyze the administrative hurdles facing the institutionalization of political analysis in aid bureaucracies. We find that programing, m anagement, and training practices across headquarters and country offi ces remain largely untouched by a political analysis agenda which suff ers from its identification with a small cross-national network of gov ernance professionals.
Keywords: DFID; United Kingdom; World Bank; aid effectiveness; foreign aid; political economy analysis